Single-step procedure for the isolation of proteins at near-native conditions from mammalian tissue for proteomic analysis on antibody microarrays - Alhamdani, Mohamed Saiel Saeed; Schröder, Christoph; Werner, Jens; Giese, Nathalia; Bauer, Andrea; Hoheisel, Jörg D. (Journal of proteome research, 2010)
The process of extracting comprehensive proteome representations is a crucial step for many proteomic studies. While antibody microarrays are an evolving and promising methodology in proteomics, the issue of protein extraction from tissues for this kind of analysis has never been addressed. Here, we describe a single-step extraction buffer for the isolation of proteins from mammalian tissues under native conditions in an effective and reproducible manner. Protein was extracted from cell lines BxPC-3 and SU.86.86, rat organs (pancreas, liver, heart and lung) and human pancreatic cancer tissues using several buffer systems that contained individual nonionic or zwitterionic detergents in comparison to commercial extraction buffers. Also, detergent combinations were used that included at least one polymeric phenylethylene glycol, a long-chain amidosulfobetaine, cholate and a zwitterionic detergent. Extracts were analyzed for protein quantity and quality. The detergent cocktails exhibited superior extraction capacity. Additionally, they demonstrated a substantially higher recovery of membrane and compartmental proteins as well as much better preservation of protein functionality. Also, they did not interfere with subsequent analysis steps such as labeling. In Western blot and antibody microarray assays, they outperformed the other buffer systems, indicating that they should also be useful for other types of proteomic studies.